1746 N.C. Sess. Laws 244 - (:unkn) unknown (My University, 1746)
Mandated that each militiaman appear with "a Gun, fit for service, a Cartouch Box, and a Sword, Cutlass, or Hanger [a type of sword], and at least Twelve Charges of Powder and Bail, or Swan Shot, and Six Spare Flints
Keywords: MILITIAS; REQUIRED POSSESSION